REGIONAL FOCUS Micro, Small and Medium Enterprises in ASEAN - Tulus T.H. Tambunan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
Definition and Development In ASEAN (the Association of Southeast Asian Nations), what constitutes a micro, small and medium enterprise (MSME) varies widely between countries (i.e. Indonesia, Thailand, Malaysia, Singapore, Cambodia, Lao People’s Democratic Republic, Viet Nam, Philippines, Brunei Darussalam, and Myanmar), or even by different agencies/organisations within a country. MSMEs may range from a part time business with no hired workers or a non-employing unincorporated business (i.e. self-employed units) such as traditional business units making and selling handicrafts in rural Java in Indonesia to small-scale semiconductor manufacturers employing more than ten people in Singapore. They may range from fast growing firms to private family firms that have not changed much for decades or have stagnated They range from enterprises that are independent businesses to those that are inextricably parts of large enterprises (LEs), such as those that belong to regional or global subcontracting networks. The only true common characteristic of MSMEs is that they are ‘not-large’; that is, whether or not a firm is really a MSME is relative. Most enterprises from the MSME category are actually very small and about 70 to 80 per cent of them employ fewer than five (5) people. Just a very small number of firms, typically ranging from 1 to 4 per cent, have more than 100 employees